2020
DOI: 10.1002/stem.3143
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Vimentinhigh/Nestinhigh proteome and tissue regenerative secretome generated by human pancreas-derived mesenchymal stromal cells

Abstract: Multipotent/mesenchymal stromal cells (MSCs) exist within a variety of postnatal tissues; however, global proteomic analyses comparing tissue-specific MSC are limited. Using human bone marrow (BM)-derived MSCs as a gold standard, we used label-free mass spectrometry and functional assays to characterize the proteome, secretome, and corresponding function of human pancreas-derived MSCs (Panc-MSCs) with a classical phenotype (CD90+/CD73+/CD105+/CD45−/CD31−). Both MSC subtypes expressed mesenchymal markers viment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 86 publications
(219 reference statements)
1
17
0
Order By: Relevance
“…Very recently, it had been shown that human pancreatic‐derived MSC are highly vimentin/nestin positive and produce a conditioned media highly enriched for proteins associated with vascular development, wound healing, and chemotaxis similar to human bone marrow‐derived MSC. Further, intrapancreatic injection of these MSC reduced hyperglycemia in streptozotocin‐treated mice 44 …”
Section: Discussionmentioning
confidence: 96%
“…Very recently, it had been shown that human pancreatic‐derived MSC are highly vimentin/nestin positive and produce a conditioned media highly enriched for proteins associated with vascular development, wound healing, and chemotaxis similar to human bone marrow‐derived MSC. Further, intrapancreatic injection of these MSC reduced hyperglycemia in streptozotocin‐treated mice 44 …”
Section: Discussionmentioning
confidence: 96%
“…Witwer et al recently highlighted the collective focus of ISCT and ISEV to further improve the guidelines for classifying MSC and MSC-generated EVs designed for therapeutic applications 26 , respectively. Indeed, the microenvironment of culture 61 and/or tissue source of origin [62][63][64][65] can lead to dynamic phenotypes and functional characteristics demonstrated by MSC in vitro 58,66 . It is also becoming evident that serial passaging and unwanted differentiation of MSC can lead to a loss of therapeutic activity 14,19,67 , such as the acquisition of a senescent secretome 68 .…”
Section: Discussionmentioning
confidence: 99%
“…All studies were approved by the Human Research Ethics Board at the University of Western Ontario (REB 12934, 12252E). Human pancreatic islets were provided by the National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) funded Integrated Islet Distribution Program (IIDP) at the City of Hope (California, USA), NIH Grant #2EC4DK098085-02.Panc-MSC were established, cultured and used to generate conditioned media (CM), as previously described 20 . CM was subsequently processed in one of three ways (Supplemental Figure 1).…”
Section: Ultrafiltration Of Msc-generated Conditioned Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreas-derived mesenchymal stromal cells (PMSCs) are one of the types of mesenchymal cells isolated from pancreatic tissues. Compared with other cells types, PMSCs are highly enriched during vascular development, chemotaxis and wound healing ( 12 ). PMSCs also possess the ability to decrease hyperglycemia in type 1 diabetes model mice after intrapancreatic injection ( 12 ).…”
Section: Introductionmentioning
confidence: 99%